Covid-19 Home Sign-Posts: Current Thinking in Health & Home for those in need - Nicholas, Diana Susan; Michael, Yvonne; Anandan, Shivanthi (Enquiry The ARCC Journal for Architectural Research, 2020)
The Integral Living Research (ILR) group advocates for five foundational principles in the urban housing environment: 1) privacy, 2) security, 3) access to healthy nourishment, 4) access to green space, and 5) self-efficacy enhancement through a culture of care and creativity. These principles have emerged from almost a decade of work in communities of need and are intended to guide designers working towards solutions to reduce stress and enhance health for urban families. In this paper, we examine and analyze best practices in WELL Buildings’ pandemic response guide among others, within the framework of housing, specifically single-family urban housing. Here, within the 2020 pandemic, best practices for alleviating the challenges of the urban single-family home in an underserved community are considered. In this analysis, five areas of focus called “COVID-19 Home Signposts” have emerged and been given additional lenses of equity and access. We describe those inequities and consider how to improve pandemic housing health for those in at-risk communities. We identify further areas for empirical study that are urgent: 1) to promote better understanding of how home, health, and housing improvement all play a role in addressing the COVID-19 pandemic; and 2) to devise appropriate strategies for addressing the fault lines in our cities and our society.